Fishery spatial plans and effort displacement in the eastern Ionian Sea: A bioeconomic modelling. (1st April 2021) - Maina, Irida; Kavadas, Stefanos; Vassilopoulou, Vassiliki; Bastardie, François
Abstract: The management of fisheries requires well-planned approaches that consider the socio-ecological costs and benefits of management options while minimising conflicts among fishing practices. We developed a framework to anticipate the cost-effectiveness of several fisheries management options, including space-time closures, gear selectivity improvements, and fishing effort reduction of eastern Ionian Sea fisheries. We also examined to what extent these fisheries could be influenced by placing new aquaculture sites into specific areas. We used a dynamic space-time model considering the effect of possible fishing effort displacement on alternative marine areas. A fine-scale distribution of 6 species of high commercial importance, for the eastern Ionian fisheries (central Mediterranean), was used together with the fishing effort distribution of trawlers, purse-seines, and small-scale fisheries to track the implications on several bio-economic indicators. The study revealed that the stocks and the fisheries economics benefited from a 10% reduction in fishing effort for all fishery sectors, while the unwanted fish catch was slightly higher. Thus, although there are notable advantages, this management option is not sufficient to support an EU regulatory framework aiming to promote more selective fishing practices and mitigate unwanted catches. However, we showed that the protection of juveniles, by imposing selectivity improvements or space-time closures on trawlers, slightly reduced the unwanted catch. Nevertheless, the benefit for the majority of stocks and fisheries economics, during the five-year simulation period, was limited. In the case of space-time closures, this is attributed to the offset due to the fishing effort displacement towards other areas. While the benefit on fish populations by improving trawl selectivity, it depends on the species. Finally, the establishment of new aquaculture units could lead to a slight re-allocation of fishing effort along the border of the new sites without substantially affecting the profit of small-scale fisheries. Such findings are useful for fisheries management and broader spatial planning in the Ionian Sea. They will provide insight to policymakers and different fishing sectors, thus enabling a more transparent and participatory decision–making process. Highlights: We study the cost-effectiveness of fisheries management options in Ionian Sea. We use a dynamic spatial bio-economic model taking into account the fishing effort displacement effect. An effort control benefits the stocks and the economy, but unwanted catch is higher. Space-time closures and selectivity improvements slightly reduce the unwanted catch. Placing new aquaculture sites has not affected the profit of small-scale fishery.